Population structure and residency of whale sharks Rhincodon typus at Utila, Bay Islands, Honduras. Issue 3 (8th August 2013) - Fox, S.; Foisy, I.; De La Parra Venegas, R.; Galván Pastoriza, B. E.; Graham, R. T.; Hoffmayer, E. R.; Holmberg, J.; Pierce, S. J.
<x xml:space="preserve">Abstract</x> There were 479 reported whale shark Rhincodon typus encounters between 1999 and 2011 at the island of Utila, which forms part of the Meso‐American Barrier Reef System (MBRS) in the western Caribbean Sea. The majority of R. typus were found to feed on small bait fish associated with various tuna species. Ninety‐five individual R. typus, ranging from 2 to 11 m total length (LT), were identified through their unique spot patterns. A significant male bias (65%) was present. There was no significant difference between the mean ± s.d. LT of female (6·66 ± 1·65 m) and male (6·25 ± 1·60 m) R. typus. Most R. typus were transient to Utila, with 78% sighted only within a single calendar year, although some individuals were sighted in up to 5 years. Mean residency time was modelled to be 11·76 days using maximum likelihood methods.